Assistance in Preparing Scientific Articles for Students of IAI Ibrahimy Genteng Banyuwangi - Ahmad Irfan Ilhami; M Rizqon Al Musafiri (Simfoni Ilmu Cindekia, 2024)
This study examines the effectiveness of a structured assistance program in enhancing the scientific article writing skills of students at IAI Ibrahimy Genteng Banyuwangi. The program was implemented through a comprehensive workshop held over half a day, featuring expert-led sessions and interactive activities. The workshop commenced with an opening session introducing the objectives and agenda, followed by two main instructional segments. The first session, delivered by Ahmad Irfan Ilhami, M.Sos., covered fundamental components of scientific writing, including title formulation, abstract creation, keyword selection, introduction, methodology, results, and discussion. The second session, led by M. Rizqon Al Musafiri, M.Pd., focused on citation practices, bibliography management, and the utilization of reference management tools such as Mendeley and Zotero. A dedicated assistance period allowed participants to apply their learning with real-time feedback from the instructors. The program concluded with a closing ceremony that reinforced community and motivation among participants. Evaluation through participant feedback indicated significant improvements in understanding and applying scientific writing principles, demonstrating the program's success in addressing common challenges faced by students. The findings suggest that targeted workshops with expert guidance and practical support are effective in developing students' academic writing competencies. Recommendations include extending the program duration, incorporating ongoing mentorship, and utilizing advanced technological tools to further enhance writing skills.